Extracellular zinc suppresses microglial inflammatory shift via Zrt- and Irt-related protein 12-dependent uptake - Aratake, Takaaki; Higashi, Youichirou; Shimizu, Takahiro; Fukata, Satoshi; Saito, Motoaki (Journal of Pharmacological Sciences, 2026)
Microglia exhibit phenotypic plasticity between anti-inflammatory M2 and pro-inflammatory M1 states, and the transition from M2 to M1 is implicated in the progression of acute brain injuries. However, the molecular mechanisms that regulate this phenotypic shift remain poorly understood. Zn2+, stored in presynaptic vesicles, is extracellularly released during pathological events, such as cerebral ischemia, and modulates microglial function. In this study, we aimed to investigate the role of extracellular Zn2+in the M2-to-M1 transition using BV2 microglial cells. Pretreatment with ZnCl2during M2 polarization significantly suppressed lipopolysaccharide-induced production of interleukin (IL)-6 and tumor necrosis factor-α following the phenotypic shift. Among the zinc transporters, Zrt- and Irt-related protein 12 (ZIP12) expression was markedly upregulated by IL-4 stimulation, and siRNA-mediated knockdown of ZIP12 abolished the Zn2+-mediated suppression of pro-inflammatory cytokine production. Furthermore, ZIP12 knockdown reduced intracellular Zn2+accumulation in IL-4-treated microglia, as revealed by FluoZin-3 fluorescence. These findings indicate that extracellular Zn2+is taken up via ZIP12 during M2 polarization and subsequently acts to suppress pro-inflammatory cytokine production, thereby restraining the shift toward an M1 phenotype.
CRIS-Team Scopus Importer:2025-12-12
Keywords: Microglia; Phenotype shift; Zinc; Zrt-; Irt-related protein 12